2018
DOI: 10.3389/fnbeh.2018.00132
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Alternating Current Stimulation With Gamma Oscillations Over the Primary Motor Cortex and Cerebellar Hemisphere Improved Visuomotor Performance

Abstract: Transcranial alternating current stimulation (tACS) can be used to modulate oscillatory brain activity. In this study, we investigated whether tACS applied over the primary motor cortex (M1) and cerebellar cortex region improved motor performance. We applied tACS (1.0 mA) to 20 healthy adults while they performed an isometric force task with some visuomotor control using their right index finger. Gamma (70 Hz) oscillations in the Experiment 1 or beta (20 Hz) oscillations in the Experiment 2 were applied for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 37 publications
1
46
2
Order By: Relevance
“…Indeed, in Experiment 2 we found that 10Hz rCB tACS, but not lM1 tACS, led to declined learning performance when compared to sham. Only few studies investigated the effect of cerebellar tACS on motor performance (Miyaguchi et al, 2018;Naro et al, 2016). These studies show that higher frequency tACS to the cerebellum led to improved motor performance, but contrary to our results, found no effect at 10Hz.…”
Section: The Effect Of 10 Hz Tacs On Motor Learning Performancecontrasting
confidence: 99%
“…Indeed, in Experiment 2 we found that 10Hz rCB tACS, but not lM1 tACS, led to declined learning performance when compared to sham. Only few studies investigated the effect of cerebellar tACS on motor performance (Miyaguchi et al, 2018;Naro et al, 2016). These studies show that higher frequency tACS to the cerebellum led to improved motor performance, but contrary to our results, found no effect at 10Hz.…”
Section: The Effect Of 10 Hz Tacs On Motor Learning Performancecontrasting
confidence: 99%
“…Moreover, transcranial alternating current stimulation (tACS) also has recently emerged as a new technique to modulate cortical oscillations and entrain brain rhythms in specific frequencies [101]. By applying cerebellar tACS at a frequency matching the basal firing rate of Purkinje cells (50 Hz), researchers have shown that tACS may modulate CBI and improve the performance of a motor tasks in healthy controls [102][103][104][105][106]. Whether these novel types of stimulation might be effective also in the treatment of cerebellar ataxias is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, evaluation of target engagement using imaging or physiologic biomarkers, as well as the assessment of "dose" by using modelling to calculate the induced currents in the brain to define individual stimulation parameters, would be essential. Moreover, the cerebellum can show significant structural changes in term of climbing fiber Purkinje cell and parallel fiber Purkinje cell wirings in cerebellar ataxia and other disorders [102][103][104][105][106], and some wiring features can be rapidly changed within days and affect cerebellar synchronization [107]. These structural changes may affect the effect of TMS and tDCS, and should be considered future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This abnormality in beta oscillations in the fronto-parietal network could indicate a crucial piece of information about impaired ability in executive processing. However, a surge in gamma band activity has been detected before and during motor performance ( 43 , 45 ) which also affected motor response time ( 46 ). It has been previously reported that gamma oscillations relied on GABAergic neuronal inhibition circuits ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of a movement task which requires motor control may be improved by modulating the activity of both M1 and the sub-cortex region rather than M1 activity alone ( 43 , 60 ). Authors of existing studies about the inhibitory control network in the human brain have repeatedly found that the activation of preSMA and r IFG is crucial for inhibitory control during stop-signal and go/no-go task.…”
Section: Discussionmentioning
confidence: 99%